IMUITA GENTE, POUCAS ANTAS ? ORIGENS, ESPAÇOS E CONTEXTOS DO MEGALITISMO • ACTAS DO II COLÓQUIO INTERNACIONAL SOBRE MEGALITISMO - Rocha, Leonor (2010)
The megalithic group of Monte da Tera was identified in 1996, during surveys of a selective nature. Subsequent fieldwork came to reveal the existence of an alignment (Sector 1) and a necropolis (Sector 2), around 100m from Sector 1. The material collected point to a chronology generally within the Iron Age I period (7th-5th century B.C). The chronological relationship between the menhirs and the necropolis (whether they are sequential or contemporary) cannot be firmly established. Thus, for the moment and for various reasons we must suppose an effective contemporaneity.